Nanomedicine of Plant Origin for the Treatment of Metabolic Disorders - Hu, Fang; Sun, Dong-Sheng; Wang, Kai-Li; Shang, Dan-Ying (Frontiers in Bioengineering and Biotechnology, 2022)
Metabolic disorders (MD) are main clinical challenges of global health that is progressing universally. An aggregate of MD such as obesity, insulin resistance, atherogenic dyslipidemia and systematic hypertension leads to the metabolic syndrome (MetS). Over few years, the MetS caused a five- and two-fold rise in diabetes mellitus type II (DM-II) and cardiovascular diseases (CVDs). Natural products specifically plants extract have insulin sensitizing, anti-inflammatory and antioxidant properties and are also considered as an alternative choice due to few adverse effects. Nanotechnology is one of the promising approaches which improves the effectiveness of treatment and limit side effects. This review mainly focuses on plant-based nano-systems in the management of MetS. Numerous nano drug delivery systems i.e., liposomes, hydrogel nanocomposites, Nano-emulsions, micelles, solid lipid and core-shell nanoparticles have been designed using plant extracts. It has been investigated that most of the nano-formulations successfully reduced the oxidative stress, insulin resistance, chronic inflammation and lipid profile in in-vitro and in-vivo studies as plant extracts interfere with the pathways of MetS. Thus, these novel plant-based nano-systems could be act as a promising candidate for clinical applications.